Legal Education and Financial Literacy of Student PayLater Users: A Normative Juridical Review - Syahmi, Taffy Faiq; Prawesthi, Wahyu; Borman, M. Syahrul (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
The development of financial technology (fintech) has changed consumption patterns in society, including among students. One popular innovation is the PayLater feature, which allows users to make transactions with delayed payment. However, this convenience may create legal and financial risks if it is not supported by adequate financial literacy and legal understanding. This study aims to analyze the role of legal education in improving students' financial literacy and in promoting the responsible use of PayLater services. The research uses a normative juridical method with a statutory approach by examining several regulations, including Law Number 8 of 1999 on Consumer Protection, the Electronic Information and Transactions Law, and Government Regulation on the Implementation of Electronic Systems and Transactions. The results show that legal education increases students’ awareness of their rights and obligations as digital consumers. Understanding PayLater regulations can also help prevent excessive consumption and misuse of digital services. Therefore, integrating legal education with financial literacy is important to foster a generation of young people who are legally aware and financially responsible in using digital financial services.